PENINGKATAN KEPERCAYAAN DIRI MAHASISWA MELALUI PELATIHAN ASERTIVITAS - Hasanah, Nur; Supriyono, Yoyon; Herani, Ika; Lestari, Sumi (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
This study was initiated by the observation that Brawijaya University psychology student batch 2007 and 2008 appeared passive in the teaching-learning process. It is acknowledged that an assertive training will be needed. The training is expected to be a pilot project or the initial steps for the implementation of studentsâ soft skills.This study aims to determine the effectiveness of assertive training to enhance student confidence. Subjects of 22 psychology students will be examined through experimental repeated measure design methodSelf confidence level was measured twice pre and post the training given. Based on the t-test test results of the self confidence level rates obtained from the pre test mean of 103.68 with standard deviations of 7.17. While the post test came up with mean of 122.45 with standard deviations of 10.05. The results of the research showed that the confidence scores of students increased significantly after the training is given. This conclusion showed that assertive training was effective to improve confidence level of the students.Keywords: self confidence, student, assertive training